Peningkatan Proses Pembelajaran Melalui Pelatihan Kuliah Online bagi Dosen - Febri Liantoni; Rachman Arief; Nanang Fakhrur Rozi; Anwar Sodik (Universitas Mathla'ul Anwar Banten, 2019)
IMPROVING LEARNING PROCESSES THROUGH ONLINE LECTURE TRAINING FOR LECTURERS. The development of information and communication technology sophistication is undeniable. One form of technological development is the Internet. With the Internet, we can receive and access information in various formats from all corners of the world. The presence of the Internet provides convenience in the world of education as a learning medium. Based on these conditions, online lecture training is conducted with the aim of improving the learning process during lectures. The training was conducted with the Google classroom application introduction material. The results obtained during the training showed very high lecturer enthusiasm. Training makes lecturers have the ability to better manage lecture materials, can arrange quiz schedules or assignments regularly every week, the ability of lecturers in interpersonal communication also increases with class collaboration.